License Plate Recognition System Using Matlab GUI For Surveillance - Venkata Srinu, M; Rao Morla, Venkateswara; Vara Prasad Baditha, Kali; Kumari. S, Vara; Maddimsetti, Srinivas (International Journal of Engineering and Technology, 2018)
License plate recognition is an essential task in applications like urban vehicle management, intelligent transportation system, traffic surveillance and parking management system. In this work, we acquire the images using the mobile app and recognize license plate details with the help of our proposed image processing model. The recognized license plate details have been displayed on a customized website. The proposed image processing model does the adaptive thresholding on the images with resolution of 1280Ã— 960. The connected component analysis using bounding boxes will be performed on threshold image. The desired plate details are highlighted by creating a region of interest for maximum magnitude row of an image based on the pixel value, then the statistical and logical operations are used to extract the candidate region. After obtaining candidate region, recognition of license plate number has been done using template matching. The complete customer details, displayed on the customized website which is connected to the database with the help of plate number. The computation time of proposed method is less than the existed methods.Â